Programming Effects of Short Prenatal Exposure to Dexamethasone in Sheep - Abouantoun, Tamara (2002)
Recent studies have linked fetal exposure to a suboptimal intrauterine environment with adult hypertension. The aims of the present study were to see whether prenatal dexamethasone administered intravenously to the ewe between 26 to 28 days of gestation (1) resulted in high blood pressure in male and female offspring and whether hypertension in males was modulated by testosterone status, and (2) altered gene expression for angiotensinogen and angiotensin type 1 (AT1) receptors in the brain in late gestation and in the adult. Basal mean arterial pressure (MAP) at 2 years of age was significantly higher in wethers exposed to prenatal dexamethasone (group D; 106 5 mm Hg, n9) compared with the control group (group S; 91 3 mm Hg, n8; P0.01). Infusion of testosterone for 3 weeks had no effect on MAP in either treatment group. At 130 days of gestation, dexamethasone administered between 26 to 28 days of gestation (group DF; n8), resulted in an increased expression of angiotensinogen in hypothalamus (in arbitrary units: 2.5 0.3 versus 1.3 0.3 in the saline group [group SF], n10; P0.05). In addition, there was higher expression of the AT1 receptors in medulla oblongata in group DF (2.6 0.6 versus 1.1 0.2 in group SF; P0.01). This effect of prenatal dexamethasone treatment was still evident in females at 7 years of age (group DA; n5; 2.6 0.5 versus 1.1 0.2 in group SA; n6, P0.05). In conclusion, brief prenatal exposure of the pregnant ewe to dexamethasone leads to hypertension in adult animals of both sexes. Most interestingly, the mechanism leading to programming of hypertension might be linked with the brain angiotensin system. (Hyperte